Liberal christianity and women's global activism : the YWCA of the USA and the Maryknoll Sisters - Izzo, Amanda L., 1977- (Rutgers University Press, 2018)
Religiously influenced social movements tend to be characterized as products of the conservative turn of the late twentieth century. Izzo argues that contrary to this view, the liberal wings of Christian churches have remained an instrumental presence in U.S. and transnational politics, and that women make up a large proportion of these activists.